ON THE SURVIVAL OF MESOCYCLOPS HYALINUS TO WATER DISSOLVED CONTAMINANTS - RAMARANI, S.; RAMALINGAM, K. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2002)
The species Mesocyclops tallinus isolated from zooplankter collection obtained from the fresh water lake (Velachery) was tested for the toxicity of NaCl, CuSO4 and detergent in varying concentrations. The results revealed that the species tolerates to both NaCl and detergent powder by osmotic adjustments. However, CuSo caused heavy mortality to the species. The study implies the importance of Zooplankter in the trophic chain of productivity and also the concern for CuSO4 pollution through fungicides and molluscicide in water bodies.